2020
DOI: 10.3357/amhp.5396.2020
|View full text |Cite
|
Sign up to set email alerts
|

Aircrew Fatigue Perceptions, Fatigue Mitigation Strategies, and Circadian Typology

Abstract: BACKGROUND: Human fatigue is an important factor within aviation, leading organizations to develop strategies to assess and mitigate associated risks. The U.S. Air Force’s Air Mobility Command (AMC) conducted the current pilot study to assess fatigue-related risks and issues in mobility operations. Specifically, we examined the relationship among fatigue perceptions, fatigue mitigation strategies, performance effectiveness graph reference, and circadian typology.METHODS: There were 21 volunteers from the Join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The research about pilots [ 40–42 , 45 , 47–49 , 51–53 , 58 , 60–62 , 64 , 65 , 67 ], truck drivers [ 50 , 56 , 63 ], and astronauts [ 43 , 44 , 46 , 54 , 55 , 57 , 59 , 66 ] included laboratory studies (e.g. conducted in stimulators) [ 43 , 44 , 53 , 56 , 57 , 59 , 66 ] and field investigations (where data acquisition occurred during normal occupational activities) [ 40–42 , 45–52 , 54 , 55 , 58 , 60–65 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research about pilots [ 40–42 , 45 , 47–49 , 51–53 , 58 , 60–62 , 64 , 65 , 67 ], truck drivers [ 50 , 56 , 63 ], and astronauts [ 43 , 44 , 46 , 54 , 55 , 57 , 59 , 66 ] included laboratory studies (e.g. conducted in stimulators) [ 43 , 44 , 53 , 56 , 57 , 59 , 66 ] and field investigations (where data acquisition occurred during normal occupational activities) [ 40–42 , 45–52 , 54 , 55 , 58 , 60–65 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…The research about pilots [ 40–42 , 45 , 47–49 , 51–53 , 58 , 60–62 , 64 , 65 , 67 ], truck drivers [ 50 , 56 , 63 ], and astronauts [ 43 , 44 , 46 , 54 , 55 , 57 , 59 , 66 ] included laboratory studies (e.g. conducted in stimulators) [ 43 , 44 , 53 , 56 , 57 , 59 , 66 ] and field investigations (where data acquisition occurred during normal occupational activities) [ 40–42 , 45–52 , 54 , 55 , 58 , 60–65 , 67 ]. Most pilots were employed by commercial airlines (to transport passengers) [ 40–42 , 45 , 47–49 , 51 , 53 , 60–62 , 64 , 65 , 67 ] with the exception of studies about maritime piloting (to guide ships) [ 52 ] and military transport operations [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circadian type may also be related to the incidence of fatigue, although its extent is unclear ( Van Dongen et al, 2006 ). One study reported that being an evening type was associated with easier adaptation to time-zone changes; another identified evening type as a risk factor for fatigue; and a third study suggested that morning types may be more likely to utilize fatigue mitigation strategies when concerned about fatigue ( Gander et al, 1993 ; van Drongelen et al, 2017 ; Morris et al, 2020 ). Other factors that may negatively affect the incidence of fatigue include disturbances in work-life balance, limited physical activity, increased duration of shift work and impaired domestic relationships ( Tvaryanas and MacPherson, 2009 ; van Drongelen et al, 2017 ).…”
Section: Contributing Factors In Aviationmentioning
confidence: 99%
“…Sleep loss is considered the primary cause of fatigue in aviators ( Caldwell et al, 2009 ; Gore et al, 2010 ; Caldwell et al, 2019 ; Morris et al, 2020 ; Wilson et al, 2020 ; Wingelaar-Jagt et al, 2021 ). However, multiple experimental, observational, and medical studies have identified biochemical mechanisms promoting the onset and maintenance of fatigue as well as sleepiness ( Raison et al, 2006 ; Raison et al, 2009 ; Dantzer et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%